Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014 IEEE 14th International Conference on Advanced Learning Technologies 2014
DOI: 10.1109/icalt.2014.203
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing a Serious Game via Open Sim Standalone Server and Scratch4OS for Introductory Programming Courses in Secondary Education: Their Effect on Student Engagement

Abstract: This study suggests a constructionist-learning framework to amplify students' engagement in introductory programming courses via a serious game that was held in Open Sim standalone server integrated with Scratch4OS. Fifty five (n=55) voluntary students from three different High schools have participated and experienced in Co.Co.I.A., a 3D mindtrap puzzle game. The empirical study findings indicated that behavioral engagement (attention, retention and energy expenditure for activity completion) does not only ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 3 publications
0
0
0
Order By: Relevance
“…For instance, comprehensive literature review, comprising 32 empirical studies from 16 countries, revealed notable improvements in students' academic performance. Among the reviewed studies are those conducted in Malaysia by Oloruntegbe and Alam (2010), in Slovenia by Herga et al (2014), in Italy by Pellas (2014), in the United States by Davenport et al (2018), and in Turkey by Kapici et al (2022). Similarly, research conducted in developing nations, such as Zimbabwe (Bhukuvhani et al, 2010), Lesotho (George & Kolobe, 2014), and Nigeria (Aliyu & Talib, 2019), has corroborated VLs' effectiveness in enhancing students' academic achievements.…”
mentioning
confidence: 95%
“…For instance, comprehensive literature review, comprising 32 empirical studies from 16 countries, revealed notable improvements in students' academic performance. Among the reviewed studies are those conducted in Malaysia by Oloruntegbe and Alam (2010), in Slovenia by Herga et al (2014), in Italy by Pellas (2014), in the United States by Davenport et al (2018), and in Turkey by Kapici et al (2022). Similarly, research conducted in developing nations, such as Zimbabwe (Bhukuvhani et al, 2010), Lesotho (George & Kolobe, 2014), and Nigeria (Aliyu & Talib, 2019), has corroborated VLs' effectiveness in enhancing students' academic achievements.…”
mentioning
confidence: 95%